Biodiesel synthesis and characterization using welted thistle plant (Carduus acanthoides) as source of new non-edible seed oil. Issue 5 (8th April 2016) - Sultana, Shazia; Ahmad, Mushtaq; Zafar, Muhammad; Ullah, Kafayat; Ashraf, Muhammad Aqeel; Ayoub, Muhammad; Tareen, Niaz Mohammad
ABSTRACT: In this work we applied base catalyzed transesterification to convert non-edible welted thistle oil ( Carduus acanthoides ) as new non-edible feedstock into biodiesel (Fatty acid methyl esters). The highest biodiesel yield of 88% was obtained using optimized reaction conditions of 70°C and 5:1 molar ratio (methanol:oil). The synthesized esters were characterize and confirmed by the application of NMR and FT-IR techniques. Gas chromatography and mass spectroscopy identified different fatty acids as palmatic acid (C16:0), oleic acid (C18:1), linoleic acid (18:2), arachidic acid (C20:0), eicosanic acid (C20:1), and erucic acid (C22:1) in the oil of welted thistle. Six corresponding methyl esters reported in welted thistle oil biodiesel includes 9-hexadecenoic acid, hexadecanoic acid, 9-octadecadienoic acid, 11-eicosanoic acid, eicosanoic acid and 13-docosenoicacid. Fuel properties, such as density @40°C Kg/L (0.8470), kinematic viscosity @ 40°C c St (4.37), flash point (95°C), cloud point (+4°C), pour point (−5°C), and sulfur contents (0.0112% wt) of the biodiesel produced were compatible with American Society for Testing and Materials D 6751 specifications.